Correlation between small dense low-density lipoprotein cholesterol and carotid artery intima-media thickness in a healthy Chinese population. Issue 1 (December 2015) - Shen, Hao; Xu, Li; Lu, Jingfen; Hao, Tianbo; Ma, Chunfang; Yang, Honglin; Lu, Zhaoyang; Gu, Yongchun; Zhu, Tonghua; Shen, Guorong
Abstract Background Small dense low-density lipoprotein cholesterol (sdLDL-C) concentration was useful in the assessment of the presence of cardiovascular diseases (CVD) and its severity. We examined whether SdLDL-C is more closely associated with carotid artery intima-media thickness (CA-IMT), a surrogate measure of atherosclerosis, than LDL-C and traditional CVD risk factors in Chinese healthy subjects. Methods We measured CA-IMT, blood pressure (BP), sdLDL-C, glucose metabolism and lipid in 183 native Chinese healthy subjects. CA-IMT was assessed by ultrasonography, and sdLDL-C concentrations were measured by a homogenous assay. Pearson's correlation coefficient analyses and Multiple regression analyses were used to examine the relationships between CA-IMT values and other clinical variables. Results The sdLDL-C level was significantly higher in males than in females (p <0.05) and there was an age effect on sdLDL-C (p <0.05). When the effects of age, gender and other traditional CVD risk factors were adjusted using multiple regression analysis. CA-IMT remained significantly associated with sdLDL-C(β = 0.437, p <0.001). Conclusions There are gender and age differences in sdLDL-C levels among a healthy Chinese population. Moreover, we found adjusted traditional CVD risk factors such as higher age, male sex, and other traditional CVD risk factors, the association between CA-IMT and SdLDL-C remained significant. sdLDL-C is may be a useful predictor in the assessment of CA-IMT in Chinese population.